After the boom: Finance and society studies in the 2020s and beyond - Amin Samman; Nina Boy; Nathan Coombs; Sandy Brian Hager; Adam Hayes; Emily Rosamond; Leon Wansleben; Carola Westermeier (Finance and Society, 2022)
The crisis of 2008 was a watershed event for the study of finance and society. There was the boom in financial markets that came to a head with the collapse of Lehman Brothers, and there was the boom in financial scholarship that followed in its wake. But what comes after this second boom? After more than decade of rapid expansion under the shadow of 2008, what comes next for the new finance studies? What are the emerging debates that matter most? Where lies the need for further theorisation and for new empirical work? In this editorial, these questions are pursued under three broad headings, each corresponding to an overarching imperative: first, the need to keep a vigilant watch on the core institutions and logics of finance; second, the need to continue expanding and deepening the field; and third, the need to persist with difficult lines of questioning.
Keywords: 300